2020
DOI: 10.3390/app10248802
|View full text |Cite
|
Sign up to set email alerts
|

A New Method for Rapid Optimization Design of a Subsonic Tandem Blade

Abstract: Tandem blade technology has been developed for years due to its capacity to bear higher aerodynamics than conventional configurations. Even so, there is still the tough problem of how to design tandem blades effectively and further improve blade performance. This paper tries to further understand the flow characteristics of tandem blades in order to present a new method of designing them under subsonic inflow conditions. Firstly, efforts were made to reveal the aerodynamic interaction between the forward blade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The researchers concluded that the use of tandem reduces the pressure loss by 20% at the design point. Subsequently, they 17 developed a new method for rapid optimization of blade design in subsonic flow in 2 dimensions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The researchers concluded that the use of tandem reduces the pressure loss by 20% at the design point. Subsequently, they 17 developed a new method for rapid optimization of blade design in subsonic flow in 2 dimensions.…”
Section: Literature Reviewmentioning
confidence: 99%